Responses of the Terrestrial Ecosystem Productivity to Droughts in China - Li, Jianguo; Wang, Yi; Liu, Lili (Frontiers in Earth Science, 2020)
The terrestrial ecosystem productivity (hereafter, TEP) is a key index of global carbon cycles and a fundamental constraint of carbon sequestration capacity, and also an important measure of ecosystem services and food security. However, the TEP has been significantly affected by the long-lasting droughts. Identifying the spatial relationship between droughts and the TEP is crucial for enhancing ecosystem services in China. Here the net primary production (hereafter, NPP) derived from the Carnegie-Ames-Stanford Approach model (CASA-NPP) and two drought indices, namely the Standard Precipitation Index (hereafter, SPI) and the Standard Precipitation Evaporation Index (hereafter, SPEI), are used to examine the spatial relationship between droughts and the NPP in China for the period of 1982-2012. Our main results have shown that: (1) China’s annual NPP has increased slowly from 3.82 to 4.35 PgC per year (hereafter, PgC/yr), while droughts have become much severer from 1982 to 2012; (2) On the 3-month timescale, the NPP in arid and semi-arid ecosystems has decreased at a rate of 1.28 TgC per month with per “unit” decrease in the drought index (indicating drier conditions). (3) Overall, the NPP in China has increased 5.71 TgC per month with per “unit” increase in the drought index (indicating wetter conditions); The contribution of this NPP increase is mainly from forests and farmlands; (4) The SPEI is a relatively more effective and sensitive index in representing China’s droughts. In southern China, the lagging period for the NPP response to droughts is about 3-month, while a 6-month lagging period is found in the arid and semi-arid ecosystems in northern China.